Thermodynamics and solar radiative analysis in Jeffery-Hamel flow through non-parallel channel by novel improved residual power series method - Mohamed Bouzidi; Mohsin Ul Haq; Ikram Ullah; Saira Shukat; Hijaz Ahmad; Mohammad Mahtab Alam; Hamid Khan; Marouan Kouki (Case Studies in Thermal Engineering)
The Jeffery-Hamel flow through convergent/divergent channel is examined in this article. It is assumed that the fluid is viscous and incompressible and flow across the non-parallel walls. Viscous fluid is further taken as an electrically conducting. Impact of Lorentz force is consider to thoroughly examine the fluid movement. Energy dissipation and solar radiation features are addressed for comprehensive analysis of thermal field. Furthermore, shrinking/stretching channels are considered for more practical application. The governing system of partial differential equations can be transformed into ordinary differential equations (ODEs) using suitable transformations. The novel IRPSM, which is sami-numerical method, is utilized to work out on the solutions of obtained system of ODEs. This method has capability to accurately predict and successfully solve such non-linear realistic problem. Validation of current method is made with other techniques and shows a reasonable correspondence. Velocity and temperature are graphically visualized for different relevant parameters. Furthermore, the local skin friction coefficient and the rate of heat transfer are examined for numerous parameters. It is observed that increasing thermal radiation parameter leads to a substantial increase in the temperature profile. Additionally, the heat transfer rate is 15 % more in diverging channel when compared with converging channel.